Manejo contable de los pasivos de la Distribuidora Touma S.A. Ditosa de la ciudad de Babahoyo, periodo 2023. - Muñoz Zapata, Andy Arturo (2024)
This research includes the elaboration of the case study carried out in Distribuidora Touma S.A. Ditosa de Babahoyo, a company dedicated to the sale of construction materials and where its main economic activity is the retail sale of such materials. It is important to carry out accounting processes for the adequate financial development, with the objective of determining the accounting management of the liabilities of the distributor in the period 2023. The designation of this research document originates from the entity's need to carry out a correct accounting process. The research methodology had a mixed qualitative and quantitative approach, in the development the following types of research were used, which were bibliographic, documentary and descriptive research. The methods applied for this research were the deductive and analytical method; in addition, the technique used was the interview where the question guide, internet, laptop, programs such as Microsoft Word, among others, were used. The line of research applied was the Financial, Administrative, Tax, Audit and Control Management with the sub line Financial, Tax and Social Commitment Management. The results showed that the distributor has an inadequate accounting management of liabilities because they do not have a predetermined accounting system, in addition to not having a support system for the accounts.